The Beneficial Effect of Intravenous Iron Administration for Chronic Heart Failure: An Updated Meta-analysis and Systematic Review - Andrianto; Lalu Galih Pratama Rinjani; Ricardo Adrian Nugraha; Primasitha Maharany Harsoyo; Michael Jonatan; Kevin Luke; Hanestya Oky Hermawan; Takashi Matsumoto (Wolters Kluwer - Medknow Publications, 2023)
Introduction: Around 50% of patients with heart failure (HF) have an existing iron deficiency (ID), with or without anemia. With such a high prevalence, more research is underway to determine whether addressing ID can improve HF. Aims: This study aimed to critically evaluate the beneficial effects of intravenous iron administration for chronic HF. Methods: Studies were searched in Medline, Embase, and Cochrane for trials investigating the effect of iron supplementation on chronic HF patients. Outcomes of HF and all-cause hospitalizations, as well as cardiovascular-related and all-cause mortalities, were observed. We calculated the odds ratios (ORs) using fixed and random-effect models. The bias was evaluated by funnel plots and Egger's regression tests. Statistical analysis was conducted using RevMan (version 5.4.1). Results: Five studies with a total sample size of 1646 subjects were included in this meta-analysis and systematic review. Four studies reported the all-cause mortality of intravenous iron supplementation for HF. None of them provided evidence for the association between intravenous iron supplementation and all-cause mortality (OR = 0.75, 95% confidence interval [CI] 0.38-1.50, P = 0.42, I2= 0%, fixed effect). Four studies established that intravenous iron therapy significantly decreased hospitalization due to HF (OR = 0.56, 95% CI: 0.34-0.94, P = 0.03, I2= 53%, random effect). Conclusion: Iron supplementation does confer the benefit of iron supplementation in patients with chronic, stable HF with regard to HF hospitalization despite not showing significant associations in all-cause hospitalization, cardiovascular death, or all-cause mortality.